DEVELOPING MARKETING STRATEGY OF POULTRY MEAT SUPPLY IN EU- 28 COUNTRIES: MULTIVARIATE ANALYSIS APPROACH - Miro Simonič; Ksenija Dumičić; Berislav Žmuk (Review of Innovation and Competitiveness, 2016)
To create a concept of the marketing strategy, it is necessary to analyse the factors affecting the purchasing decisions of consumers. For the variables: production, import, export, and manufacturer's price we examine their impact on the marketing of poultry meat in the EU-28 in 2009 and 2011. Countries are grouped into clusters, their properties are analysed in relation to the mentioned variables. With multiple regression analysis, we find that there is a statistical correlation between high production and de-pending on the variable, and between the imports and exports as the independent vari-ables. Based on the analysed data in the researched countries, we conclude that the qualitative development of the production of poultry meat required implementing sophis-ticated agricultural policy with low inputs prices and exploit all available spare re-sources.